National Football League Head, Neck and Spine Committee's Concussion Diagnosis and Management Protocol: 2017-18 season. Issue 14 (16th March 2018) - Ellenbogen, Richard G; Batjer, Hunt; Cardenas, Javier; Berger, Mitchel; Bailes, Julian; Pieroth, Elizabeth; Heyer, Robert; Theodore, Nicholas; Hsu, Wellington; Nabel, Elizabeth; Maroon, Joe; Cantu, Robert; et al.
Abstract : One of the National Football League's (NFL) Head, Neck and Spine Committee's principal goals is to create a 'best practice' protocol for concussion diagnosis and management for its players. The science related to concussion diagnosis and management continues to evolve, thus the protocol has evolved contemporaneously. The Fifth International Conference on Concussion in Sport was held in Berlin in 2016, and guidelines for sports concussion diagnosis and management were revised and refined. The NFL Head, Neck and Spine Committee has synthesised the most recent empirical evidence for sports concussion diagnosis and management including the Berlin consensus statement and tailored it to the game played in the NFL. One of the goals of the Committee is to provide a standardised, reliable, efficient and evidence-based protocol for concussion diagnosis and management that can be applied in this professional sport during practice and game day. In this article, the end-of-season version of the 2017–18 NFL Concussion Diagnosis and Management Protocol is described along with its clinical rationale. Immediate actions for concussion programme enhancement and research are reviewed. It is the Committee's expectation that the protocol will undergo refinement and revision over time as the science and clinical practice related to concussion in sports crystallise